Blurring the boundaries of mass media communication?: Interaction and user-generated content on online news sites - Landert, Daniela (Texts and discourses of new media, 2014)
This study investigates the communicative setting of one form of online mass media communication, namely online news sites published by professional news organisations. Such sites provide options for audience interaction that go far beyond what was possible in earlier forms. One of the questions this raises concerns the extent to which this might contribute to a blurring of boundaries between 1) mass and interpersonal communication, 2) editorial content and user-generated content, and 3) the roles of journalists and readers. In order to approach these questions, I develop a model for the communicative situation on online news sites which makes it possible to explore these boundaries. Data from five British online news sites show that mass communication and user interaction are combined in various ways on these platforms, without making it necessary to give up the distinction between mass and interpersonal communication. Concerning user-generated content, the news sites show marked differences as to how clearly they differentiate it from editorial content. For the role of readers this means that they can turn into sources for journalistic news writing. The last part of the study contextualises these findings by adopting a diachronic view on the development of interactive forms on news sites, relating them to earlier reader feedback in print newspapers and looking at some of the most recent trends with respect to the integration of social media.
Gesehen am 04.04.2024